On the solution of the growth model with investment-specific technological change - Jesús Fernández-Villaverde; Juan Francisco Rubio-Ramírez (Federal Reserve Bank of Atlanta, 2004)
Recent work by Greenwood, Hercowitz, and Krusell (1997 and 2000) and Fisher (2003) has emphasized the importance of investment-specific technological change as a main driving force behind long-run growth and the business cycle. This paper shows how the growth model with investment-specific technological change has a closed-form solution if capital fully depreciates. This solution furthers our understanding of the model, and it constitutes a useful benchmark to check the accuracy of numerical procedures to solve dynamic macroeconomic models in cases with several state variables.
Keywords: 330